2015
DOI: 10.1590/0001-3765201520140471
|View full text |Cite
|
Sign up to set email alerts
|

Linking environmental drivers with amphibian species diversity in ponds from subtropical grasslands

Abstract: Amphibian distribution patterns are known to be influenced by habitat diversity at breeding sites. Thus, breeding sites variability and how such variability influences anuran diversity is important. Here, we examine which characteristics at breeding sites are most influential on anuran diversity in grasslands associated with Araucaria forest, southern Brazil, especially in places at risk due to anthropic activities. We evaluate the associations between habitat heterogeneity and anuran species diversity in nine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…Earlier studies highlighted the importance of pond size and edge vegetation to anuran diversity ( Parris and McCarthy 1999 , Burne and Griffin 2005 , Bastazini et al 2007 , Vieira et al 2007 , Xavier and Napoli 2011 , Dória et al 2015 , Gonçalves et al 2015 ). Furthermore, microenvironments composed of vernal pools with different edge vegetation structures and percentage of vegetation cover on water surface better explained the different compositions of anuran communities in Parnaíba River Delta.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies highlighted the importance of pond size and edge vegetation to anuran diversity ( Parris and McCarthy 1999 , Burne and Griffin 2005 , Bastazini et al 2007 , Vieira et al 2007 , Xavier and Napoli 2011 , Dória et al 2015 , Gonçalves et al 2015 ). Furthermore, microenvironments composed of vernal pools with different edge vegetation structures and percentage of vegetation cover on water surface better explained the different compositions of anuran communities in Parnaíba River Delta.…”
Section: Discussionmentioning
confidence: 99%
“…Others have found that the species richness of amphibians is influenced by factors such as temperature, geography, and precipitation (e.g., Ortiz‐Yusty et al, ; Soares & Brito, ). Nonetheless, these factors are not the only studied, other studies have also found that anuran diversity has been determined as a response to either different types of vegetation, distance to water bodies or environmental heterogeneity (e.g., Goncalves, Crivellari, & Conte, ; Ribeiro et al, ). Here, from the regression analysis, we also found that precipitation could have a strong effect on the diversity of amphibians (SR‐PD; Figure , Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…Andropogon lateralis and Aristida jubata), the increase in biomass production and the recruitment/regrowth of woody plants during warm months (Soares et al, 2005;Overbeck et al, 2006). The grassland vegetation structure offers a great diversity of food items, calling sites, and shelters (for protection from predation and high solar exposure) for grassland-specialist anurans (Xavier and Napoli, 2011;Gonçalves et al, 2015). Grasslands are of major importance for Leptodactylidae anurans which include grassland-specialist species (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that seasonality in temperature, photoperiod and rainfall might control the peaks of anuran reproduction and richness in subtropical and temperate regions, whereas abundant rainfall might sustain continuous anuran reproduction in tropical regions Both et al, 2008;Canavero et al, 2008). Further, climate seasonality can differentially influence the vegetation heterogeneity and resource quality of an area, as the effects of climate seasonality depend on the habitat type (Maragno et al, 2013;Gonçalves et al, 2015). Here, we evaluated the seasonal variations in the composition of anuran assemblages from forest and grassland habitats, which are two habitats differently influenced by climate seasonality.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation